대상질환군으로 본 의·한 협진연구 경향 분석 - 전은희; 이현주; 조민경; 김남권; 이인; Jun, Eun-hee; Lee, Hyeon-joo; Cho, Min-kyoung; Kim, Nam-kwen; Lee, In (대한한방내과학회지, 2020)
Objectives: The purpose of this study was to analyze trends in Korean-Western Collaborative Medicine studies by disease group. Methods: Articles published until May 2020 were searched in domestic databases (NDSL, RISS, KISS, DBPIA, and KoreanTK) using the keywords '한양방', '양한방', '협진', '협의진료', '의한의', '의·한의', and '통합의학'. The articles were analyzed according to the publication year, journal type, research methodology, and disease group using the major and intermediate classifications of the Korean Standard Classification of Diseases (KCD-7). Results: In total, 112 articles were selected. The most frequent major disease groups were disease codes G, C (D), I, and M, in that order. The medium disease groups numbered 41 and most commonly involved collaborative studies on cerebrovascular diseases. Among the three top KCD-7 major group diseases, publications on Group C (D) were increasing significantly, publications on Group G were slightly increasing, but, publications on Group I decreased in the 2010s compared to the 2000s. Conclusions: In this study, we analyzed the frequent disease groups treated with domestic Korean-Western medicine in collaborative studies using the major and medium classifications of KCD-7. Well-designed clinical trials and economic evaluation research are needed, and this study can provide directions for future collaborative studies using Korean-Western medicine.